Archive Management of Tienuk Riefki: Strategies And Solutions - Rulli Meilia (Institut Seni Indonesia Yogyakarta, 2023)
The curation of “Tienuk Riefki Archives and Memorabilia Exhibition: Maestro of Javanese Tradisional Bridal Makeup Art” made this choice derived from the culture and values contained in tradisional bridal makeup. Tienuk Riefki is one of the bridal makeup artists who still adheres to the standard. The method used is a qualitative method in which the variable is a means or a tool to analyze and the author will examine a problem with an individual or certain in depth with a historical approach. This method is used to find out about personal, and tradisional Javanese bridal makeup, especially Yogyakarta. The process of implementing the practice of curation in the